Effectiveness of Training Program Implementation at the Neutral Ponorogo Course and Training Institute: An Islamic Economic Perspective - Fauzah Agustina; Khoirun Nisak; Raisha Salisa Ahmad (Niqosiya: Journal of Economics and Business Research, 2025)
Introduction: The Course and Training Institution (LKP) plays a strategic role in improving the quality of human resources. LKP Neutral Ponorogo is one of the institutions that offers a batik training program to enhance the skills of participants. However, as the program progresses, it is important to assess whether it is truly effective in providing an impact, particularly in improving the quality of human resources for students. This study aims to analyze the effectiveness and impact of the training program implemented by LKP Neutral Ponorogo. Research Methods: This study uses a qualitative method. Data were collected through interviews, observations, and documentation, then analyzed through reduction, presentation, and drawing conclusions. The validity of the data was tested using triangulation techniques, and research informants included leaders, staff, and training participants at LKP Neutral. Results: The research findings indicate that the training program at LKP Neutral Ponorogo has been quite effective in improving human resource quality, while also contributing to economic empowerment and enhancing participants' work ethics from an Islamic economic perspective. Despite facing several challenges, the program has had a positive impact, as reflected in the participants' improved knowledge, skills, and abilities. Conclusion: The batik training program conducted by LKP Neutral Ponorogo demonstrates the potential of vocational education in shaping a skilled, ethical, and economically empowered society. With continuous improvement and support, such initiatives can serve as a model for enhancing human resource development by Islamic economic values.